Moral Debates in the Ottoman Empire during the First World War - Burcu Belli (Avrasya İncelemeleri Dergisi)
Çiğdem Oğuz The Struggle Within: “Moral Crisis” on the Ottoman Homefront During the First World War. London: Bloomsbury Publishing, 2021, 248 p., ISBN: 9781838607098